Adaptive aromaticity in osmapentalene and osmapyridinium complexes with carbone ligands. (24th October 2022) - You, Feiying; Qiu, Rulin; Zhu, Jun
Abstract: Discovery of species with adaptive aromaticity, being aromatic in both the lowest‐lying singlet and triplet states (S0 and T1 ), is a significant challenge because cyclic conjugated complexes are commonly aromatic in one state only according to Hückel's and Baird's rules. On other hand, the carbone ligands containing two lone pair electrons at the carbon(0) atom have attracted considerable attention from both theoretical and experimental chemists recently. Here, we carry out density functional theory (DFT) calculations on osmapentalene and osmapyridinium complexes with carbone ligands to examine their aromaticity in both the S0 and T1 states. It is found that these complexes can possess adaptive aromaticity, supported by various aromaticity indices including the harmonic oscillator model of aromaticity (HOMA), nucleus‐independent chemical shift (NICS), anisotropy of the induced current density (ACID), electron density of delocalized bonds (EDDB), and the change of heat of hydrogenation (∆∆H). Our findings expand the scope of the concept of adaptive aromaticity, inviting experimental chemists' verification to enrich aromatic organometallic chemistry. Abstract : DFT calculations suggest that osmapentalene and osmapyridinium complexes with carbone ligands can be aromatic in both lowest singlet and triplet states, expanding the scope of the concept of adaptive aromaticity and inviting experimental chemists' verification to enrich the aromatic organometallic chemistry.